MANGO TREE HASRATES IN A SHORT STORY OF DENGAR KELUHAN POHON MANGGA: STUDY ON PSYCHOANALYSIS OF LACAN - Devi Cintia Kasimbara (Universitas Putera Batam, 2020)
Dengar Keluhan Pohon Mangga (DKPM) is the story written by Maria Amin during the Japanese colonial era. The author uses the metaphor of